The Meaning Behind Concepts in Different Subject Disciplines and Cultures: Reflections on developments of Europe and of European Secondary Education - Daniliuk, Alexander Yaroslavovich; Faktorovich, Alla Arkadievna (International Dialogues on Education Journal, 2017)
The article discusses the development of the content of secondary education in Europe in the context of globalization and the information society. The authors emphasize the urgency to move from education based on knowledge to education based on working with the meaning behind denominated objects. The authors argue that the methodological application of new pedagogical thinking and new technologies, a re-organization of the educational process, but also new educational content are methods and factors which can move knowledge-transfer forward. There must be a productive introduction of these methods and factors to pedagogy, a synthesis of existing practices of interdisciplinary teaching and the use of the unrealized potential of modern information technologies to build an original model for the world of European education. To achieve this, a new project for a European educational network is necessary. It will provide not only economic and social integration, but also intellectual understanding and cooperation.